(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2004)
This paper is an overview of the gastropods from the Toarcian to Lower Kimmeridgian fissure fillings of Rocca Busambra. They are the most diverse and richest Jurassic faunas known from the pelagic sediments of the western Tethys. 224 species, 137 of them new, were recognized. The main feature of the structure of these assemblages is the high number of new taxa and the concomitant presence of an archaic stock with Triassic affinities, and a group advancing the appearance of the modern caenogastropod taxa. These features give these assemblages an important place in the reconstruction of the evolution of the whole class.